Sharing research data in a connected world for connected decisions: Lessons learned from the CGIAR Research Program on Water, Land and Ecosystems (WLE) - CGIAR Research Program on Water, Land and Ecosystems (CGIAR Research Program on Water, Land and Ecosystems, 2021)
Trends in data science demonstrate the utility of big, open access data in addressing global challenges such as land degradation, food and nutrition security, biodiversity loss and climate change. As vastly more data becomes accessible, new skill sets are required in order to collect, manage, curate, store, share and analyze these datasets. This brief provides lessons learned on collecting, managing and utilizing research data from a 10-year research-for-development program that aimed to advance research and innovation in the areas of soil, land, water and ecosystems. While institutional changes will take time, this paper advocates an integrated approach as a more immediate solution for managing large amounts of research data – from the outset of projects until the end with a specific focus on data ethics and reusability. Resources, capacities and organizational structures and norms must be built around these objectives.